La atención y la comprensión lectora en estudiantes del décimo grado de educación general básica de la Escuela John F. Kennedy, cantón Macará, 2023 -2024. - Sánchez Carcelén, Maryuri Liceth (2024)
The Curricular Integration Work aimed to analyze the relationship between attention and reading comprehension of students in the tenth grade of basic education at the John F. Kennedy Macará School, 2023-2024. The research had a quantitative, descriptive, correlational and transversal approach, with a non-experimental design. The Toulouse – Piéron Test was applied to evaluate Attention and the Tapia & Silva Reading Comprehension Test in the sample of 18 students, an intentional non-probabilistic sampling was used; Statistical data processing was obtained using the Excel program, SPSS 26 software, and Kendall's Tau-b rank correlation coefficient and the Pearson correlation coefficient interpretation table. The results of the attention evaluation revealed that 38.89% of the sample obtained a low level, 33.33% are at a very low level; Regarding reading comprehension, 66.7% of those investigated are at a low level while 27.8% are at a very low level. The correlation between attention and reading comprehension reached a Kendall's Tau-b value of .472, this value indicates on the Pearson r coefficient Interpretation scale that there is a range of positive correlation of medium magnitude between both variables. It is concluded that there is a positive correlation of medium magnitude between attention and reading comprehension. Therefore, the alternative hypothesis is accepted that says: If there is a statistically significant relationship between attention and reading comprehension in tenth grade students